Protamines from liverwort are produced by post-translational cleavage and C-terminal di-aminopropanelation of several male germ-specific H1 histones - D'Ippolito, Robert Anthony (J Biol Chem, 2019)
Protamines are small, highly-specialized, arginine-rich, and intrinsically-disordered chromosomal proteins that replace histones during spermiogenesis in many organisms. Previous evidence supports the notion that, in the animal kingdom, these proteins have evolved from a primitive replication-independent histone H1 involved in terminal cell differentiation. Nevertheless, a direct connection between the two families of chromatin proteins is missing. Here, we primarily used electron transfer dissociation MS-based analyses, revealing that the protamines in the sperm of the liverwort Marchantia polymorpha result from post-translational cleavage of three precursor H1 histones. Moreover, we show that the mature protamines are further post-translationally modified by di-aminopropanelation, and previous studies have reported that they condense spermatid chromatin through a process consisting of liquid-phase assembly likely involving spinodal decomposition. Taken together, our results reveal that the interesting evolutionary ancestry of protamines begins with histone H1 in both the animal and plant kingdoms.